2016
DOI: 10.4172/2155-6148.1000607
|View full text |Cite
|
Sign up to set email alerts
|

Study of Attenuation of Cardiovascular Response during Laryngoscopy and Intubation Using Two Different Doses of Pregabalin as Premedication in Controlled Hypertensive Patients- A RCT

Abstract: Introduction: Laryngoscopy and tracheal intubation are powerful noxious stimuli that should be attenuated. Effect more severe in hypertensive patients. The present study evaluated the safe and clinically effective dose of oral pregabalin as premedication for attenuation of pressor response of airway instrumentation in controlled hypertensive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
2
3
1
Order By: Relevance
“…Although the HR increase was not completely attenuated by pregabalin, the drug obviously mitigated the HR after laryngoscopy and intubation, which is in agreement with findings reported by Meena et al showing no significant difference in the HR before and after premedication [15]. Immediately after laryngoscopy and intubation, the HR increased significantly in all groups, but the increase was smallest in group III (PG300); as such, the heart HR was not completely attenuated by pregabalin but was definitely mitigated after laryngoscopy.…”
Section: Discussionsupporting
confidence: 82%
“…Although the HR increase was not completely attenuated by pregabalin, the drug obviously mitigated the HR after laryngoscopy and intubation, which is in agreement with findings reported by Meena et al showing no significant difference in the HR before and after premedication [15]. Immediately after laryngoscopy and intubation, the HR increased significantly in all groups, but the increase was smallest in group III (PG300); as such, the heart HR was not completely attenuated by pregabalin but was definitely mitigated after laryngoscopy.…”
Section: Discussionsupporting
confidence: 82%
“…The above facts explain that 150 mg single oral dose of pregabalin was effective in attenuating maternal anxiety without any sedation effect on mothers in the current study. In contrast to previous studies Singh et al [13] and Doddaiah et al [20], the present study results revealed no effects of single oral dose of 150 mg pregabalin on maternal mean heart rates, mean arterial blood pressures, serum glucose, and cortisol levels during intubation and these finding can be explained first, pregabalin attenuate stress response in a dose-dependent manner in accordance with Meena et al [21] who studied the effects of two different oral doses of pregabalin 150 mg and 300 mg one hour before surgery compared to oral placebo for attenuating cardiovascular response to laryngoscopy and intubation in controlled hypertensive patients and found that 150 mg oral pregabalin and oral placebo were associated with significant rising in the heart rate and mean arterial blood pressure compared to 300 mg after instrumentation of airway. Second, the mechanism by which pregabalin attenuates the stress response of intubation is still unknown and all explanations are just diligence as it may act on inhibiting Ca++ outflow from muscles with squally inhibition of relaxation of smooth muscles [22].…”
Section: Discussioncontrasting
confidence: 59%
“…Meena R et al 15 conducted a study on attenuation of cardiovascular response during laryngoscopy and intubation using different doses of oral pregabalin in 150mg and 300mg in controlled hypertensive patients. Oral pregabalin in a dose of 300mg was a better premedicant compared to 150mg as it not only blunted the arterial pressor response to laryngoscopy and intubation, but also provided anxiolysis with reduction of intra-operative anaesthetic drug requirement and maintained haemodynamic stability without significant adverse effects.…”
Section: Discussionmentioning
confidence: 99%